Automated construction project progress monitoring system [electronic resource] - 325279 Zubair Ahmed Memon; Muhd. Zaimi Abd. Majid, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2007